2015
DOI: 10.1007/s12010-015-1801-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Phosphorus-Accumulating Fungi and Their Potential for Phosphorus Removal from Waste Streams

Abstract: While bacteria have been primarily studied for phosphorus (P) removal in wastewater treatment, fungi and their ability to accumulate intracellular polyphosphate are less investigated. P-accumulating fungal strains were screened from soybean plants and surrounding soil by flask cultivation with potato dextrose broth and KH2PO4 in this study. Mucor circinelloides was selected for its high efficiency in P removal efficiency and high cellular P content. Neisser staining and growth-curve analysis confirmed that M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…The cited study reported reductions of PO 4 3 -P in the range of those reported in the present study: 28.3–44%. Interestingly, a positive relationship between fungal cellular P content and increasing organic nitrogen in wastewater have been reported (Ye et al 2015). Thus, fungi can display increasing P removal when applied to different waste streams.…”
Section: Discussionmentioning
confidence: 98%
“…The cited study reported reductions of PO 4 3 -P in the range of those reported in the present study: 28.3–44%. Interestingly, a positive relationship between fungal cellular P content and increasing organic nitrogen in wastewater have been reported (Ye et al 2015). Thus, fungi can display increasing P removal when applied to different waste streams.…”
Section: Discussionmentioning
confidence: 98%
“…Especially for M. circinelloides cells, lower P removal efficiency than that of control means inherent P in fungal cells was partially released. At pH from 2 to 4, the fungal cells showed the best P removal performance (P removal efficiency was 80.3, 84.7 and 82.6% at pH of 2, 3 and 4, respectively), because more insoluble P was dissolved to soluble P, the bioavailable form for M. circinelloides cells to assimilate (Ye et al ., ), and M. circinelloides can grow under a condition with low pH (Xia et al ., ). With the pH increased from 3 to 7, the reduction of P solubility led to a decreasing trend of P removal efficiency by FBT.…”
Section: Resultsmentioning
confidence: 99%
“…b–d). The decrement of TN was larger than that of TAN, indicating that M. circinelloides cells were able to assimilate N in other forms besides TAN, such as nitrate and urea (Ye et al ., ). It was observed that the concentration of TN and TAN in FBT group increased obviously after 24 h, because of the anaerobic bioconversion of proteins existing in DMW to amino acids and then to ammonia, caused by oxygen consumption in the flasks (Cheng and Liu, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of P in Poly-P granules has also been reported in these organisms. For instance, Mucor circinelloides reached a cellular P-content of 7.08% (Ye et al, 2015). Several yeasts were also reported as Paccumulating organisms, and the mechanisms of P-accumulation have already been studied at a genetic level in Saccharomyces cervisiae (Watanabe et al, 2008).…”
Section: Phosphorus Recycling By Other Organismsmentioning
confidence: 99%